(untitled) (European Journal of Interdisciplinary Studies, 2018)
This paper is part of the chainwork that deals the syntax study of the dialect of the province of Chameria, a prominent and conservative language of the south of Albania. This study is the second in this regard. Initially, we were dealing with the intonation of Chams and mainly with its syntactic value (Troplini 2016). For the syntax of the of the regional variety of Chameria, there is no previous effort. In this paper, as a basic literature, we have only used our previous works for the Cham in the sociolinguistic framework, where we were dealing with phonetic, morphological, lexical, historical linguistics etc. Our first effort also underlines the first difficulties of this syntactic treatment, as well as the objectives that need to be fulfilled in the perspective, through a deep scientific monograph that will conclude a long-term gap in the study of the cham variety in terms of syntax. The method we used is the inductive one. The work has been based on a qualitative research basis. We are based on a series of direct interviews with elderly speakers of this province who were born mainly in Chameria and subjected to ethnic cleansing. This generation well preserves the most southern and extreme Albanian talk. In this study, we intend to highlight some of the most important phenomena of the Cham variety which will then serve for a deep work in terms of syntax.